2019
DOI: 10.1002/bbb.2053
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost recycling production of pectinase to increase the yield and quality of Muzao jujube juice by Aspergillus niger

Abstract: A low‐cost recycling system for the production of pectinase was built to improve the yield and quality of Muzao date juice and to reduce production costs. An Aspergillus niger strain, Gyx086, was selected from 20 A. niger strains on potato agar plates containing Muzao date residues, and the strain was used to produce an enzyme cocktail with high pectinase activity using Muzao date residues as the medium. The high pectinase activity level was therefore used in the production of Muzao date juice. Under optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A. niger strains produce cellulase, xylanase, amylase, and proteinase [ 42 - 44 ], which allow the utilization of inexpensive agricultural residues ( e.g. , wheat bran, corn core, and peanut cake) for enzyme production [ 45 , 46 ]. In future studies, a recombinant A. niger strain will be used for the low-cost production of PoxaEnPG28C [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…A. niger strains produce cellulase, xylanase, amylase, and proteinase [ 42 - 44 ], which allow the utilization of inexpensive agricultural residues ( e.g. , wheat bran, corn core, and peanut cake) for enzyme production [ 45 , 46 ]. In future studies, a recombinant A. niger strain will be used for the low-cost production of PoxaEnPG28C [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the factors affecting the flavonoid yield, fermentations were performed with different initial pH levels (5, 6, 7, 8, and 9), temperatures (25, 30, 35, 37, 40 °C), leaf powder concentrations (1-5 g L −1 ), and fermentation times (12,24,36,48,60,72, and 84 h). All the experiments, under different conditions, were performed in triplicated.…”
Section: Single Factors Optimizationmentioning
confidence: 99%
“…33 The utilization of the lignocellulolytic enzyme and lignocellulose-degrading microbe has been studied for a long time. Several studies have shown their potential in extracting various types of value-added and bioactive compounds such as phenolic compounds, 34 carbohydrates, 35 fruit juice, 36 and pigments. 37 So far, many fungi and bacteria have been found capable of producing lignocellulolytic enzymes such as cellulases, [38][39][40][41] hemicellulases, [42][43][44] peroxidases, and laccases.…”
mentioning
confidence: 99%